EKSPRESI HONORIFIK DAN STATUS SOSIAL DALAM MASYARAKAT JAWA - Dwi Atmawati (Balai Bahasa Kalimantan Barat, 2020)
Various titles and honorifics expressions in Javanese society has become particular interest for writer to analyze. The honorific expressions described in this paper include the title of nobility and greeting word in Daerah Istimewa Yogyakarta. The research uses equality method to review particular lingual unit using determiner tools beyond language. Based on the data and analysis it is known that titles of the nobles are rara, gusti raden ajeng, gusti raden ayu, kanjeng pangeran harya, gusti bendara raden mas, gusti bendara raden ajeng, gusti bendara raden ayu, bendara raden mas, bendara kanjeng pangeran, bendara raden ajeng, bendara raden ayu. Where greeting word based on social class, the writer classifies it into three, upper, middle, and lower class. The greeting word on upper class society are such as papi, mami, papa/papah, mama/mamah, daddy, mom, tante, om, oma, opa, eyang, jeng. The greeting word on middle class society are such as ayah, ibu, bapak, bunda, abi, ummi, paman, bibi, mas, mbak. The greeting word on lower class society are such as pak/bapak, mbok/embok/simbok, biyung, mbakyu, pakdhe, mbokdhe, paklik, bulik. The greeting word are decreasing in number are embok/mbok/simbok dan biyung. Defining the greeting word is tightly associated to social status of the speakers.